Pengaruh Digital Marketing terhadap Keputusan Pembelian Konsumen pada Usaha Berbasis Syariah - Reza Savitri (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to examine the effect of digital marketing on consumer purchasing decisions in Sharia-based businesses. This research employed a quantitative approach using a survey method. The population consisted of consumers who had purchased products from Sharia-based businesses, while the sample included 100 respondents selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire and analyzed through validity, reliability, and normality tests, followed by simple linear regression, t-test, and coefficient of determination (R²) using SPSS software. The findings indicate that digital marketing has a positive and significant effect on consumer purchasing decisions in Sharia-based businesses. The more effective the implementation of digital marketing through social media, websites, online marketplaces, and content marketing, the greater the likelihood that consumers will make purchasing decisions. Furthermore, the implementation of Sharia principles such as honesty, transparency, and ethical business practices in digital marketing activities enhances consumer trust, which ultimately strengthens purchasing decisions.